METABOLOMIC APPROACHES APPLIED TO THE STUDY OF CERVICAL CANCER: A SYSTEMATIC REVIEW - Almeida, Natalia Damasceno; Matos, Marcos Almeida; Brito, Milena Bastos; Souza, Amancio Jose de (Brazilian Journal of Oncology, 2022)
Background: Cervical cancer (CC) is the fourth leading cause of cancer among women in the world. Metabolomics can provide a deeper understanding of the underlying metabolic alterations associated with its pathophysiology.Objective: To systematically analyze metabolomic approaches and findings used in the study of cervical cancer.Selection Criteria: Studies that included the use of metabolomics, obtained through biological samples, from patients diagnosed with CC.Data collection and Analysis: The review was conducted according to the PRISMA guidelines, and registered in PROSPERO. The terms of Medical Subject Headings (MeSH) and Health Sciences Descriptors (DeCS) corresponding to “Metabolomics” and “Cervical Cancer” were used as descriptors. Article quality was reviewed based on the QUADOMICS criteria.Results: A total of 17 articles were selected for systematic review. Study quality evaluation using QUADOMICS demonstrated heterogeneous results. The main changes in metabolite levels associated with cervical cancer were identified in alanine, creatine, valine, tyrosine, isoleucine, phosphatidylcholine, acetate, lactate and β-glucose. Some amino acid levels were reduced in patients with CC and changes in energy metabolism pathways were observed. Eight articles tested the diagnostic capacity of metabolomics, obtaining results for sensitivity > 90%, specificity between 73% and 99% and AUC between 0.78 and 0.99.Conclusion: The results suggest that patients with CC present alterations in energy metabolism, amino acids and glycerolphospholipids, pointing to a potential group of specific biomarkers.
Keywords: Metabolomics; Uterine Cervical Neoplasms; Metabolic Networks and Pathways; Biomarkers